Investigating the Physical Properties of FeCu and its Potential use in Dye Sensitized Solar Cells - AlAwadhi, Mariam Yousif Yousif (2021)
A Master of Science thesis in Mechanical Engineering by Mariam Yousif Yousif AlAwadhi entitled, “Investigating the Physical Properties of FeCu and its Potential use in Dye Sensitized Solar Cells”, submitted in July 2021. Thesis advisor is Dr. Wael Abuzaid and thesis co-advisor is Dr. Abdul Hai Al Alami. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).